IN SILICO ANALYSIS OF ANTIFUNGAL POTENTIAL, PHYSICOCHEMICAL PROPERTIES, DRUG-LIKENESS, AND TOXICITY OF BIOACTIVE COMPOUNDS OF Cannabis spp. AS BIOFUNGICIDE CANDIDATES FOR CONTROLLING FUNGAL DISEASES IN OIL PALM PLANTS: ANALISIS IN SILICO POTENSI ANTIFUNGI, SIFAT FISIKOKIMIA, DRUG-LIKENESS, DAN TOKSISITAS SENYAWA BIOAKTIF Cannabis spp. SEBAGAI KANDIDAT BIOFUNGISIDA UNTUK PENGENDALIAN PENYAKIT JAMUR PADA TANAMAN KELAPA SAWIT - Okduartus Ryan; Muhammad Pirmansyah; Togu Pasternar Manik; seto kuncoro jati; Glenn Augusthio; uswatun nurul khoiriah; dodi iskandar (PT. ROCE WISDOM ACEH, 2026)
This study aimed to evaluate the antifungal potential, physicochemical properties, drug-likeness characteristics, and toxicity profiles of bioactive compounds from Cannabis plants using in silico approaches. The analyses were conducted using PASS Online, SwissADME, and PKCSM platforms to identify potential natural antifungal agents for controlling fungal diseases in oil palm plants. PASS analysis demonstrated that several compounds exhibited strong antifungal activity, particularly glycoside flavonoids and cannabinoid compounds. Flavosativaside, orientin 7-glucoside, and flavocannabiside showed the highest Probability of Active (Pa) values, indicating promising antifungal potential. Cannabinoid compounds such as cannabidiol (CBD), cannabigerolic acid (CBGA), and tetrahydrocannabivarin also displayed considerable antifungal activity due to their lipophilic properties, which facilitate penetration into fungal cell membranes. SwissADME analysis revealed that most compounds possessed favorable physicochemical and pharmacokinetic characteristics, including acceptable lipophilicity, water solubility, and bioavailability. Several flavonoids and cannabinoids fulfilled major drug-likeness criteria, including Lipinski, Ghose, Veber, Egan, and Muegge rules, suggesting good potential for biological interaction and absorption. Simple flavonoids and cannabinoids exhibited more balanced polarity and membrane permeability than glycoside flavonoids, which generally had higher molecular weights and polar surface areas. PKCSM toxicity prediction indicated that most compounds were non-mutagenic and non-hepatotoxic, although several showed potential mutagenic or hepatotoxic effects that warrant further investigation. Environmental toxicity analysis suggested that most compounds exhibited low to moderate ecological toxicity, supporting their potential application as environmentally friendly biofungicides. Overall, the results indicate that Cannabis-derived compounds possess significant potential as natural antifungal agents for controlling fungal diseases in oil palm plantations. The integration of PASS, SwissADME, and PKCSM analyses provides an efficient preliminary screening strategy to identify effective and safe bioactive compounds before further in vitro and in vivo studies.